The PhysioNet / Computers in Cardiology Challenge 2008: T-Wave Alternans - Moody, GB (2008)
The 9th annual PhysioNet/Computers in Cardiology challenge invited participants to measure T-wave alternans (TWA) in a set of 100 two-minute electrocardiograms that included subjects with a variety of risk factors for sudden cardiac death (including ventricular tachyarrhythmias, transient myocardial ischemia, and acute myocardial infarctions), healthy controls, and synthetic ECGs with calibrated amounts of artificial TWA. The participants’ TWA estimates were used to develop a ranking of the 100 test cases in order of TWA content, and the Kendall rank correlation coefficient between this reference ranking and each individual participant’s ranking of the 100 cases was calculated as a score (between −1 and 1; actual scores were between 0.11 and 0.92). The challenge yielded insights into the strengths and weaknesses of classic and novel TWA analyses, open-source implementations of a variety of methods, and a set of freely available ECGs with reference rankings of TWA content.